The changing context for small farms and implications for their future - Peter Hazell (Danish Institute for International Studies (DIIS), 2007)
The majority of farms in the developing world are small (less than 2 hectares) and they are home to the majority of the rural poor. Their future will have an important bearing on whether poverty and hunger can be halved by 2015. However, small farms are seriously challenged today in ways that make their future precarious. Globalization and rising per capita incomes in many countries are changing the nature and composition of demand for agricultural products. At the same time, marketing chains are changing and are becoming more integrated and more demanding of quality and food safety. This is creating new opportunities for higher value production for farmers who can compete and link to these markets, but for many other small farms the risk is that they will simply be left behind. In developing countries, small farmers also face unfair competition from rich country farmers in many of their export and domestic markets, and they no longer have adequate support in terms of basic services and farm inputs. And the spread of HIV/AIDS is further eroding the number of productive farm family workers, and leaving many children as orphans with limited knowledge about how to farm. Left to themselves, these forces will curtail opportunities for small farms, overly favor large farms, and lead to a premature and rapid exit of many small farms. If most small farmers are to have a viable future, then there is need for a concerted effort by governments, NGOs and the private sector to create a more equitable and enabling economic environment for their development. This must include assistance in forming effective marketing organizations, targeted agricultural research and extension, revamping financial systems to meet small farm credit needs, improved risk management policies, better education and training for nonfarm jobs and where all else fails, targeted safety net programs. These interventions are possible and could unleash significant benefits in the form of pro-poor agricultural growth. For many countries, the alternative is a dramatic increase in rural poverty and waves of migrants to urban areas that could overwhelm available job opportunities, urban infrastructure and support services.
Keywords: 330; Kleinbäuerliche Landwirtschaft; Armut; AIDS; Ländliche Entwicklung; Entwicklungsländer